1997
DOI: 10.2307/2269508
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemical Response of Forest Ecosystems to Simulated Chronic Nitrogen Deposition

Abstract: Reported in this paper are foliar chemistry, tree growth (above-and belowground), soil chemistry, nitrogen cycling (net mineralization and nitrification) and soil N 2 O flux responses to the first 6 yr of chronic nitrogen amendments at the Harvard Forest (Massachusetts, USA). A 70-yr-old red pine (Pinus resinosa Ait.) stand and a 50-yr-old mixed hardwood stand received control, low nitrogen (50 kg·ha Ϫ1 ·yr Ϫ1 ), high nitrogen (150 kg·ha Ϫ1 ·yr Ϫ1 ), and low nitrogen plus sulfur treatments, with additions occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
226
3
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 159 publications
(256 citation statements)
references
References 37 publications
25
226
3
2
Order By: Relevance
“…Previous studies at this site also found low N 2 O fluxes (Bowden et al 1991, Magill et al 1997. Our new NO data suggest that N gas fluxes are larger, and more responsive to N deposition, than previously thought.…”
Section: Challenge #2 -How To Account For the Episodic Nature Of N Gasupporting
confidence: 67%
“…Previous studies at this site also found low N 2 O fluxes (Bowden et al 1991, Magill et al 1997. Our new NO data suggest that N gas fluxes are larger, and more responsive to N deposition, than previously thought.…”
Section: Challenge #2 -How To Account For the Episodic Nature Of N Gasupporting
confidence: 67%
“…However, more and more attention is being paid to denitrification process in forests under increasing N deposition due to the high global warming potential of N 2 O (Hall and Matson 1999;Levy-Booth et al 2014). Although some studies have shown that N deposition and fertilization to forest ecosystems have minor effects on soil N 2 O emission (Magill et al 1997), there is mounting evidence that excessive N deposition to forest ecosystems, especially to N-unlimited forest ecosystems, has promoted soil N 2 O emission (Butterbach-Bahl et al 1998;Gundersen et al 2012;Hall and Matson 1999;Jassal et al 2011;Pilegaard et al 2006;Zhang et al 2008). For example, Hall and Matson (1999) found that N addition stimulated N 2 O emissions in both phosphorus (P)-limited and N-limited tropical forest soils, with a greater stimulation in the P-limited forest.…”
Section: Denitrification and N 2 O Emissionmentioning
confidence: 99%
“…Soil material was collected at the Harvard Forest Long-Term Ecological Research Site in north-central Massachusetts, U.S.A., from an approximately 50-y-old mixed hardwood stand established following abandonment from pastures in the early 1900's (Magill et al, 1997). Total biomass in the stand was 111 t ha À1 , and was dominated by black oak (Quercus velutina Lam.…”
Section: Site Descriptionmentioning
confidence: 99%